(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2026)
Phraseological units constitute an essential component of linguistic and cultural systems, as they preserve the historical experience, collective worldview, and social values of a particular speech community. In contemporary linguocultural studies, phraseology is regarded not merely as a set of fixed expressions, but also as a reflection of national mentality, cultural stereotypes, and communicative traditions. Among various thematic groups of phraseological units, beverage-related expressions occupy a significant place due to their close connection with everyday life, hospitality practices, ritual behavior, and ethical evaluation.